(untitled) (Eurasian Medical Research Periodical, 2023)
The scientific basis presented in our article is the high scientific and technical progress, the level of the modern development of home nursing, characterized by an increased need for highly qualified specialists, encourages higher medical faculties to increase the requirements for the quality of professional staff training doctors. Currently, the emphasis is on the formation of a high level of worldview and professional skills of students, their erudition, culture, morals, and moral personal qualities